Health literacy research in Malaysia: a systematic review - Abdullah, Adina; Salim, Hani Syahida; Ng, Chirk Jenn; Liew, Su May (2017)
Introduction: Health literacy has emerged as an important determinant of health and a key component of self-care and patient centered medicine. In Malaysia, the recent National Health Morbidity Survey found that the adult l health literacy level was worryingly low. Local research in health literacy is urgently needed. The aim of this systematic review is to identify and synthesize research publications on health literacy carried out in Malaysia.